Ionic conduction study on biopolymer electrolytes based carboxymethyl cellulose/kappa carrageenan doped NH4BR - Shui, Jun Kit (2016)
Since the introduction of polymer based electrolytes in 1970s, numerous polymers were particularly interesting especially the using of biopolymer have been investigated. This type of electrolyte material was introduced in order to avoid many of the problems encountered when using in electrochemical devices with liquid electrolyte. Due to the reason, the present research with the development of blending carboxymethyl cellulose/kappa carrageenan (CMC/KC) was carried out by doping with ammonium bromide (NH4Br) based biopolymer electrolytes. The CMC/KC doped different amount of NH4Br were successfully prepared via solution casting technique and were characterized by using Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and Electrical Impedance Spectroscopy (EIS) technique. In FTIR analysis it shows that the interaction between CMC/KC and NH4Br has occurred and due to the protonation of H+ towards CMC/KC backbone. XRD analysis showed that the amorphouness had increased when NH4Br was added and lead to the increasing in ionic conductivity. The optimum of ionic conductivity was observed at 4.25x10-4 Scm-1 for sample containing with 30 wt. % NH4Br. The significant changes from FTIR data analysis was used to determine transport properties of CMC/KC-NH4Br by using deconvolution method. From the deconvolution method, it can be found that the ionic conductivity affected by mobility of ions and diffusion coefficient for ion migration in this present research.